2020
DOI: 10.1186/s12951-020-0580-1
|View full text |Cite
|
Sign up to set email alerts
|

Size-isolation of superparamagnetic iron oxide nanoparticles improves MRI, MPI and hyperthermia performance

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) are extensively used for magnetic resonance imaging (MRI) and magnetic particle imaging (MPI), as well as for magnetic fluid hyperthermia (MFH). We here describe a sequential centrifugation protocol to obtain SPION with well-defined sizes from a polydisperse SPION starting formulation, synthesized using the routinely employed co-precipitation technique. Transmission electron microscopy, dynamic light scattering and nanoparticle tracking analyses show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 44 publications
7
90
0
1
Order By: Relevance
“…Due to their biocompatibility and chemical stability, iron-oxide nanoparticles made of magnetite (Fe 3 O 4 ) are suitable for labels in biomedical applications [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Their synthesis is investigated in a wealth of literature, indicating that the superparamagnetic limit highly depends on the synthesis procedure [ 28 , 29 , 30 ].…”
Section: Simulation Methods and Parametersmentioning
confidence: 99%
“…Due to their biocompatibility and chemical stability, iron-oxide nanoparticles made of magnetite (Fe 3 O 4 ) are suitable for labels in biomedical applications [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Their synthesis is investigated in a wealth of literature, indicating that the superparamagnetic limit highly depends on the synthesis procedure [ 28 , 29 , 30 ].…”
Section: Simulation Methods and Parametersmentioning
confidence: 99%
“…To address this important technical challenge, several research groups have demonstrated experimentally that the MPI gradient field can localize MFH heating [21,22,[61][62][63][64]. Despite using a 300 kHz magnetic field, we and others have demonstrated localized heating to millimeter-scale resolution.…”
Section: Fundamentals Of Gradient-based Localizationmentioning
confidence: 99%
“…Note that these theoretical predictions are based on zero-temperature dynamics and interacting nanoparticle assemblies on a profoundly complex structure. In contrast, many laboratory experiments consider simpler structures or super-paramagnetic assemblies designed for specific applications; see, for example, [51][52][53]. Apart from the finite temperature and a continuous spin symmetry, this topological equivalence can be lifted, leading to a smooth hysteresis loop in the presence of long-range dipolar interactions; the impact of the substrate on which the assembly is realised; and the distributed size of nanoparticles.…”
Section: Spin Dynamics and Hysteresis Loops In Different Assembliesmentioning
confidence: 99%